Seasonal behavior of Thalassia testudinum (Hydrocharitaceae) metabolites - Hernández Rivera, Yasnay; González García, Kethia; Valdés-Iglesias, Olga del Rosario; Zarabozo Silva, Akaena; Portal Ríos, Yessica; Laguna Granja, Abilio; Martínez Daranas, Beatriz; Rodríguez García, María; Gutiérrez Cuesta, Richard (Revista de Biología Tropical, 2016)
<!--[if gte mso 9]> 800x600 <![endif]--> The marine angiosperm Thalassia testudinum, commonly known as turtle grass, is a dominant seagrass that grows in the Caribbean Sea shelf associated to Syringodium filiforme. The hydroalcoholic extract of T. testudinum is rich in polyphenols; the most abundant metabolite in this extract is thalassiolin B, a glycosilated flavonoid with skin damage repairing properties, and antioxidant capacity among others. The present study aimed at generating information about the seasonal behavior of secondary metabolites, as well as to study the antioxidant capacity of the T. testudinum leaves extract, collected monthly during 2012 from the Northeast coastline of Havana, Cuba. For this study, spectrophotometric methods were used to determine the concentrations of polyphenols, flavonoids, anthocyanins, soluble carbohydrates and proteins, chlorophylls a and b, and antioxidant activity of the extracts. In general, results demonstrated seasonal variations of the analyzed parameters. Extracts prepared from the vegetal material collected in October and November showed the highest values of polyphenols (58.81 ± 1.53 and 52.39 ± 0.63 mg/g bs, respectivally) and flavonoids (44.12 ± 1.30 and 51.30 ± 0.67 mg/gdw, respectively). On the contrary, the lowest values of polyphenols were found in extracts of leaves collected in July and August (15.51 ± 0.84 and 13.86 ± 0.48 mg/g,respectively). In accordance with these results, the lower value of Inhibitory Concentration (IC50) was obtained to get a 50 % of maximal effect on free radical scavenging activity with the extracts prepared from leaves collected in October and November, and less significant IC50 was obtained from the extract prepared from leaves collected in August (5.63 mg/mL). A negative correlation (r= -0.694) was observed in this study between the content of polyphenols and the IC50 necessary to get the half of its antioxidant maximal effect. The high correspondence between the maximum values of polyphenols, flavonoids, carbohydrates and proteins in October and November, revealed a close relationship between these metabolites found in the extract of T. testudinum. Our hypothesis about the annual variation in the concentration of these metabolites was validated; and these results will support the correct harvesting of T. testudinum leaves for biotechnology and industrial purposes. <!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->